Envolvimento de receptores dopaminérgicos do tipo D2 do colículo inferior e da amígdala basolateral na expressão do medo condicionado e incondicionado em ratos machos e fêmeas - Alves, Camila de Oliveira (Universidade Federal de São Carlos, 2026)
Substantial evidence indicates that dopamine is one of the most active neuromodulators underlying fear/anxiety states. Depending on the threatening condition (conditioned or unconditioned), blockade of D2-like dopaminergic receptors may reduce or increase aversiveness, suggesting a dual role for dopamine in aversive states. The present study aimed to evaluate the effects of D2-like dopaminergic receptors blockage in the inferior colliculus (IC) and basolateral amygdala (BLA) on the expression of unconditioned and conditioned fear in male and female rats. The study was conducted in two stages. First, a systematic literature review was performed to identify publications investigating the role of D2-like receptors in conditioned and unconditioned fear, examining methodological characteristics and main findings. In the second stage, an experimental study assessed the effects of sulpiride (a D2-like antagonist) administration into the IC (Experiment 1) or BLA (Experiment 2) in male and female Wistar rats subjected to the elevated plus maze (EPM) and contextual fear conditioning tests. The systematic review indicated that systemic administration of D2-like drugs has a notable impact on both innate and learned fear. In general, antagonists tend to increase unconditioned fear, whereas agonists reduce it; moreover, both agonists and antagonists decrease conditioned fear. These effects are attributed to the involvement of distinct neural circuits in these fear states. Regarding the experimental findings, Experiment 1 showed that intra-IC injections of sulpiride decreased open-arms entries and time spent in the open arms of the EPM, as well as exploration of open-arm extremities, but only in females in metestrus/diestrus. In conditioned fear, sulpiride reduced freezing time in the test and retest in males, proestrus/estrus females, and metestrus/diestrus females. Thus, intra-IC sulpiride produced a sex- and estrous cycle-dependent pro-aversive effect on unconditioned fear and a generalized anti-aversive effect on conditioned fear. In Experiment 2, intra-BLA sulpiride decreased time spent in the open arms of the EPM only in males and reduced head-dipping and rearing in males and proestrus/estrus females. In conditioned fear, sulpiride reduced freezing time in the test and retest in males, proestrus/estrus females, and metestrus/diestrus females. Thus, intra-BLA sulpiride also produced a sex- and estrous cycle-dependent pro-aversive effect on unconditioned fear and a generalized anti-aversive effect on conditioned fear. Taken together, the findings reinforce the dual role of dopamine in aversive states, with D2-like receptors modulating unconditioned fear and mediating the expression of conditioned fear, and extend the literature by demonstrating the relevance of dopaminergic signaling in the IC and BLA in both cases. Moreover, the study reveals sex- and estrous cycle-dependent differences, indicating that female gonadal hormones modulate dopaminergic influences on unconditioned fear, highlighting the importance of including females and the pioneering nature of this investigation.
Involvement of D2-like dopaminergic receptors in the inferior colliculus and basolateral amygdala in the expression of conditioned and unconditioned fear in male and female rats
Keywords: Dopamina; Colículo inferior; Amígdala basolateral; Medo; Ansiedade; Condicionamento aversivo contextual; Labirinto em cruz elevado; Diferença sexual; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA FISIOLOGICA::PSICOBIOLOGIA; 3. Saúde e Bem-Estar